2016
DOI: 10.1097/ajp.0000000000000329
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Problems are Associated With Chronic Pain Over and Above Mutual Associations With Depression and Catastrophizing

Abstract: Pain, mood problems and sleeping difficulties are often comorbid and contribute to reduced physical function and quality of life for those suffering from chronic pain. However, the way in which these factors interact is unclear. Until recently it was thought that the effect of sleep on pain and physical function was simply a result of its common association with mood problems. However, a growing body of research suggests that sleep may have a unique contribution.Objectives: The aim of this study was to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
20
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 56 publications
(71 reference statements)
7
20
1
1
Order By: Relevance
“…The same can be said of the causal relationship between pain and a lack of adequate sleep. People who suffer from pain may find it harder to sleep because of the pain [50].…”
Section: Discussionmentioning
confidence: 99%
“…The same can be said of the causal relationship between pain and a lack of adequate sleep. People who suffer from pain may find it harder to sleep because of the pain [50].…”
Section: Discussionmentioning
confidence: 99%
“…Among healthy college students volunteering in a study evaluating sleep quality and pain catastrophizing, self‐reported sleep quality with PSQI was identified as an important factor influencing pain catastrophizing among African Americans (Goodin et al., ). In a cohort of 101 chronic pain patients, insomnia measured by the PSQI correlated with pain catastrophizing scores (Roberts and Drummond, ). Likewise in patients with chronic myofascial temporomandibular pain, pain catastrophizing scores were significantly correlated with PSQI scores (Buenaver et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Það sama má segja um orsakatengsl verkja og svefns. Fólk sem líður verki getur átt erfiðara með að sofa vegna verkjanna (Roberts & Drummond 2016).…”
Section: Stjórnmál and Stjórnsýslaunclassified